Living the Hiplife: Celebrity and Entrepreneurship in Ghanaian Popular Music. Jesse Weaver Shipley. 2013. London and Durham, NC: Duke University Press. 329pp. - Erlmann, Veit (International Library of African Music, 2013)
pages: 187-189
Keywords: Popular music; Entrepreneurship; Celebrities; African Music; Ghana; Hiplife